Ceramic reinforced contact line and preparation method thereof

Through the preparation method of ceramic reinforced contact lines, combined with Cu and Ag alloys and Al2O3 and Mg2O ceramic powders, multi-process processing is adopted to solve the problems of insufficient wear resistance and electrical performance of contact lines, and achieve wear resistance improvement and electrical performance Optimized, extends service life and reduces maintenance costs.

CN119114945APending Publication Date: 2024-12-13XIAN XIDIANGUANG CABLE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411229194.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The wear resistance of existing contact lines is limited, which affects electrical performance, and has short replacement cycle and high maintenance costs, which have problems with service life and economic benefits.

Method used

Using ceramic reinforced contact line preparation method, Cu powder, Ag powder, Al2O3 powder and Mg2O powder are mixed in the corresponding proportion, and through isostatic sintering, hot forging, pushing, surface treatment, rolling and drawing processes, it is formed. Ceramic reinforced contact lines improve their wear resistance and electrical properties.

Benefits of technology

It significantly improves the wear resistance and electrical performance of the contact line, extends the service life, reduces maintenance costs, reduces wear by more than 50%, and increases service life by more than 2 times, maintaining the mechanical and electrical performance of the raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114945A_ABST
    Figure CN119114945A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic-reinforced contact line and a preparation method thereof, and belongs to the technical field of railway catenaries, and the preparation method comprises the following steps: mixing Cu powder and Ag powder to obtain copper-silver alloy powder, then mixing the copper-silver alloy powder with Al2O3 powder and Mg2O powder to obtain synthetic powder, and sequentially carrying out isostatic pressing sintering, hot forging, pushing, surface treatment, rolling and drawing to obtain the ceramic-reinforced contact line. By introducing a ceramic phase into an existing contact line product alloy series, the strength, hardness, electrical performance and wear resistance of a contact line material at the present stage are greatly improved while the conductivity of the material is reduced as much as possible, the maintenance cost of a contact network is reduced, and meanwhile, a new material choice is provided for speed increase of rail transit; the original processing technology is broken, and a brand new alloy series is provided. The strength of the contact wire can reach 580 MPa or above, the conductivity is controlled to be 80% IACS or above, the surface hardness can reach 85 HB or above, abrasion is reduced by 50% or above, the service life of the contact wire is prolonged by two times or above, and the service life of the contact wire is far beyond that of other types of contact wire products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway contact networks, and in particular relates to a ceramic-reinforced contact wire and a preparation method thereof. Background Art

[0002] The contact wire is an important component of the rail transit contact network traction power supply. The wear caused by long-term contact and friction with the pantograph is the main reason limiting the service life of the contact wire. If the cross-sectional area wears up to 20%, it needs to be replaced. The current railway overhaul management regulations temporarily set the service life of the contact wire at 15 years. However, in the subway, due to factors such as high driving frequency and frequent vehicle starts and stops, the wear of the contact wire increases sharply. The shortest replacement cycle of the contact wire in the subway line has reached less than 1 year. The wear of the contact wire greatly increases the driving safety and contact network maintenance costs in railway and subway lines.

[0003] At present, there are two main means to reduce the wear of the contact wire. One is to improve the carbon slide plate that is in direct contact with the contact wire and increase the lubrication effect of the carbon slide plate to reduce the wear of the contact wire; the other is to reduce the wear of the contact wire itself by enhancing the wear resistance of the contact wire. The Chinese patent application with application number CN201610630067.2 discloses a production process of a high-wear-resistant copper alloy contact wire. The invention relates to the technical field of wear-resistant contact wire production and discloses a production process of a high-wear-resistant copper alloy contact wire, including the following steps: (1) A-grade cathode copper is continuously cast in a smelting device, and after casting, it is cooled with cooling circulating water to prepare an upper copper rod; (2) The upper copper rod is continuously extruded in a continuous extruder to prepare a contact wire blank; (3) A drawing unit is used to prepare a finished contact wire. The contact wire prepared by the present invention has excellent wear resistance. The invention talks about an alloy-reinforced wear-resistant contact wire, the principle of which is to enhance the strength and hardness of the material through alloying to achieve the purpose of improving the wear resistance of the contact wire. The biggest certainty of this scheme is that the strength and hardness of the material improved by alloying are limited, and as the mechanical properties of the material improve, the electrical performance of the contact will drop sharply, the energy consumption of the contact network will increase, and the power-on temperature of the contact network will increase. There are certain risks, and the wear resistance improvement effect is limited.

[0004] In view of the challenges faced by existing contact lines in reducing contact line wear, such as limited improvement in wear resistance, impact on electrical performance, short replacement cycle, and high cost and maintenance pressure, it is urgently necessary to conduct modification research on them, so as to enhance the wear resistance of contact line products and increase the service life of contact lines without reducing the mechanical and electrical properties of raw materials. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a ceramic-reinforced contact wire and a preparation method thereof, so as to solve the technical problems of the existing contact wire having limited improvement in wear resistance, affecting electrical performance, short replacement cycle, and high cost and maintenance pressure.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention discloses a method for preparing a ceramic-reinforced contact wire, comprising:

[0008] Cu powder and Ag powder are mixed to obtain copper-silver alloy powder, which is then mixed with Al2O3 powder and Mg2O powder to obtain synthetic powder. The powder is sequentially subjected to isostatic pressing, hot forging, extrusion, surface treatment, rolling and drawing to obtain a ceramic-reinforced contact wire.

[0009] Preferably, the mass percentage of Cu powder in the copper-silver alloy powder is 99.85-99.95%wt, and the mass percentage of Ag powder is 0.05-0.15%wt; in the synthetic powder, the mass percentage of Al2O3 powder is 0.35-0.45%wt, the mass percentage of Mg2O powder is 0.25-0.35%wt, and the mass percentage of copper-silver alloy powder is 99.25-99.35%wt.

[0010] Preferably, the purity of the Cu powder is greater than 99.98%, and the particle size is greater than 400 mesh; the purity of the Ag powder is greater than 99.99%, and the particle size is greater than 400 mesh; the particle size of the Al2O3 powder is greater than 1000 mesh; and the particle size of the Mg2O powder is greater than 1000 mesh.

[0011] Preferably, the isostatic pressing sintering conditions include: a sintering temperature of 900-1000° C., a pressure of 3-5 MPa, a sintering time of 1-2 h, and sintering into a rod with an outer diameter of 70-80 mm.

[0012] Preferably, the hot forging conditions include: heating to 650-700° C. for rotary forging, and forging to a diameter of 55-75 mm.

[0013] Preferably, the extrusion conditions include: heating to 450-500° C., keeping warm for 30-60 minutes, and then extruding into rods with a diameter of 30-35 mm, so that the average grain size inside the rods reaches 0.02-0.03 mm.

[0014] Preferably, the surface treatment conditions include: rolling and peeling; 3 to 6 times of peeling, and the peeling thickness is 0.5 to 1 mm.

[0015] Preferably, the diameter of the contact wire blank after rolling is 20 to 30 mm.

[0016] Preferably, the number of drawing passes is 3 to 6.

[0017] The present invention also discloses a ceramic-reinforced contact wire, which is prepared by the above preparation method. The strength of the ceramic-reinforced contact wire is 550-594 MPa, and the resistivity at 20°C is 0.02190-0.02299 Ω·mm 2 / m, Brinell hardness is 81~86HB, wear is 0.001mm 2 / Ten thousand bow sorties.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The invention discloses a method for preparing a ceramic-reinforced contact wire, which aims to combine a ceramic material with higher wear resistance with the contact wire, and to enhance the wear resistance of the contact wire product by introducing a ceramic phase without reducing the mechanical and electrical properties of the raw materials, so that the service life of the contact wire is increased by more than 2 times. Al2O3 and Mg2O ceramic phase powders are fully mixed with Ag and Cu powders in corresponding proportions, and then sintered, so that the ceramic powders are fully distributed to copper and silver, so as to achieve the purpose of full dispersion and uniform distribution. By introducing the ceramic phase into the existing contact wire product alloy series, while reducing the material conductivity as much as possible, the strength, hardness, electrical properties and wear resistance of the current contact wire material are greatly improved, the maintenance cost of the contact network is reduced, and a new material selection is provided for the speed increase of rail transit, breaking the original processing technology and providing a new alloy series. Al2O3 and Mg2O phases are formed in situ in the copper-silver alloy through an isostatic pressing process; the internal defects of the material casting process are eliminated through a hot forging process; the fine-grained internal structure is obtained through a pushing process; the surface defects of the material are eliminated through a surface treatment process; and the finished contact wire product is obtained through a cold rolling + drawing process. The present invention introduces a ceramic phase into the copper-based alloy of the contact wire product, thereby improving the strength and hardness of the material while minimizing the impact on the electrical properties of the material. At the same time, the ceramic second phase can effectively improve the wear resistance of the contact wire during use and reduce the wear of the contact wire. The strength can reach more than 580MPa, the conductivity is controlled at more than 80%IACS, the surface hardness can reach more than 85HB, the wear is reduced by more than 50%, and the service life of the contact wire is increased by more than 2 times, far exceeding other types of contact wire products.

[0020] The present invention also discloses a ceramic-reinforced contact wire obtained by the above-mentioned preparation method. The advantages of the ceramic-reinforced contact wire include: 1. The strength and wear resistance of the existing contact wire are significantly improved; by introducing a ceramic phase into the copper-based alloy, the strength and hardness of the material are successfully improved while maintaining the original conductivity of the material. The addition of the ceramic phase makes the strength of the contact wire reach more than 580MPa, far exceeding the ordinary contact wire products. The ceramic phase also greatly enhances the wear resistance of the contact wire, and its surface hardness can reach more than 85HB, and the wear is reduced by more than 50%, thereby effectively extending the service life of the contact wire, and the improvement can reach more than 1 times. 2. Optimizing electrical performance: Although the ceramic phase is introduced, the present invention successfully controls the conductivity of the contact wire to more than 80% IACS by precisely controlling the material composition and processing technology, ensuring that its electrical performance in rail transit is not significantly affected. 3. Reduced maintenance costs: Due to the significant improvement in strength and wear resistance, the contact wire prepared by the present invention is less worn during use, thereby reducing the maintenance frequency and cost of the contact network, which has significant economic benefits for rail transit operators. Fourth, it provides new material options; the present invention provides new material options for speeding up rail transit. Traditional contact wire materials often have a trade-off relationship between strength, wear resistance and conductivity, but the present invention breaks this limitation and provides a new alloy series. The ceramic-reinforced contact wire prepared by the present invention shows significant beneficial effects in terms of strength, wear resistance, electrical performance, maintenance cost and material innovation, providing a new high-performance, low-maintenance contact wire material for the rail transit field. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a flow chart of the method for preparing the ceramic-reinforced contact wire disclosed in the present invention. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0024] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0025] See also Figure 1 The present invention discloses a flow chart of the preparation method of the ceramic-reinforced contact wire; as can be seen from the figure, the preparation method of the ceramic-reinforced contact wire includes: mixing Cu powder and Ag powder to obtain copper-silver alloy powder, then mixing with Al2O3 powder and Mg2O powder to obtain synthetic powder, and sequentially undergoing isostatic pressing sintering, hot forging, extrusion, surface treatment, rolling and drawing to obtain a ceramic-reinforced contact wire. The present invention will greatly improve the strength, hardness, electrical properties and wear resistance of the current contact wire material by introducing ceramic phases into the existing contact wire product alloy series. The present invention uses an isostatic pressing process to form Al2O3 and Mg2O phases in situ in the copper-silver alloy; uses a hot forging process to eliminate internal defects in the material casting process; uses an extrusion process to obtain a fine-grained internal structure; uses a surface treatment process to eliminate surface defects in the material; and uses a cold rolling + drawing process to obtain a finished contact wire product.

[0026] The present invention mixes Cu powder and Ag powder to obtain copper-silver alloy powder. Copper powder has good conductivity and low cost, but weak oxidation resistance; silver powder has excellent conductivity and oxidation resistance, but the resource is relatively scarce and the cost is high. Mixing the two to prepare copper-silver alloy powder can combine the advantages of the two, maintain high conductivity, improve oxidation resistance, and reduce costs. In addition, alloying may also bring about an increase in hardness and wear resistance, which is crucial to the service life of the contact line.

[0027] Then, it is mixed with Al2O3 powder and Mg2O powder to obtain synthetic powder. Al2O3 and Mg2O are used as ceramic reinforcement materials to significantly improve the mechanical properties and thermal stability of the synthetic powder. Aluminum oxide has high hardness, high wear resistance and good chemical stability, while magnesium oxide has low thermal expansion coefficient and good thermal conductivity. These characteristics make the synthetic material with the addition of ceramic powder show stronger stability and durability when subjected to high temperature, high pressure and corrosive environment. After isostatic pressing, hot forging, extrusion, surface treatment, rolling and drawing in sequence, a ceramic-reinforced contact wire is obtained. After Al2O3 and Mg2O ceramic phase powders are fully mixed with Ag and Cu powders in corresponding proportions, they are sintered to fully distribute the ceramic powder to copper and silver, so as to achieve the purpose of full dispersion and uniform distribution.

[0028] Isostatic sintering is a densification process carried out under high temperature and pressure, which can form a closer bond between powder particles, thereby improving the density and strength of the material. This step helps to eliminate the pores between powder particles, reduce defects, and improve the overall performance of the material.

[0029] Hot forging is a process of plastic deformation of materials at high temperatures, which can further improve the material's structure and mechanical properties. Through hot forging, the grains can be refined, the strength and toughness of the material can be improved, while internal stress can be eliminated and the tendency to deformation and cracking can be reduced. This is crucial for the stable operation of the contact line under complex working conditions.

[0030] Extrusion is a metal forming process that uses high pressure to squeeze the material into the desired shape. This step helps to further refine the material's organizational structure and improve the material's density and uniformity. At the same time, extrusion can also accurately control the size and shape of the product to ensure that the contact line meets the design requirements.

[0031] Surface treatment can improve the surface properties of materials, such as improving wear resistance, corrosion resistance and conductivity. For contact wires, good surface properties help reduce contact resistance, improve conductivity efficiency, and extend service life. In addition, surface treatment can also beautify the appearance of the product and improve the overall quality of the product.

[0032] Rolling is a process that compresses and deforms the material through rollers. It can make the material thinner in the thickness direction while stretching it in the width and length directions. The rolling process helps to further refine the grains and improve the strength and toughness of the material. At the same time, rolling can also improve the surface finish and flatness of the material, ensuring good contact between the contact wire and the conductive rail.

[0033] Drawing is a process that stretches a material through a die. It reduces the material in diameter while extending it in length. The drawing process helps to further increase the strength and toughness of the material, while improving the dimensional accuracy and surface quality of the material. For contact wires, drawing helps to obtain a more uniform and smooth cross-sectional shape, ensuring good electrical conductivity and mechanical properties.

[0034] The purpose of the present invention is to provide a ceramic reinforced contact wire and a preparation method thereof. The contact wire is prepared by fully mixing ceramic phase powders such as Al2O3 and Mg2O with Ag and Cu powders in corresponding proportions, and then sintering the mixture so that the ceramic powders are fully distributed to the copper and silver to achieve the purpose of full dispersion and uniform distribution.

[0035] The present invention aims to combine ceramic materials with higher wear resistance with contact wires. On the basis of not reducing the mechanical and electrical properties of the raw materials, the wear resistance of the contact wire products is enhanced by introducing ceramic phases, thereby increasing the service life of the contact wire by more than 2 times.

[0036] The present invention introduces a ceramic phase into the copper-based alloy of the contact wire product, thereby improving the strength and hardness of the material while minimizing the impact on the electrical properties of the material. At the same time, the ceramic second phase can effectively improve the wear resistance of the contact wire during use and reduce the wear of the contact wire. The strength can reach more than 580MPa, the conductivity is controlled at more than 80%IACS, the surface hardness can reach more than 85HB, the wear is reduced by more than 50%, and the service life of the contact wire is increased by more than 1 times, which is far superior to other types of contact wire products.

[0037] The present invention introduces ceramic phase into the alloy material, which greatly improves the strength and wear resistance of the material while reducing the conductivity of the material as much as possible, reduces the maintenance cost of the contact network, and at the same time provides a new material option for speeding up rail transit, breaks the original processing technology, and provides a new alloy series.

[0038] 1. The present invention adopts powder metallurgy, and 99.85-99.95%wt of Cu powder and 0.05-0.15%wt of Ag powder are fully mixed to obtain copper-silver alloy powder, and then 0.35-0.45%wt of Al2O3 powder, 0.25-0.35%wt of Mg2O powder and 99.25-99.35%wt of copper-silver alloy powder are mixed to obtain synthetic powder;

[0039] 2. The present invention adopts isostatic pressing sintering, the sintering temperature is 900-1000°C, the pressure is 3-5MPa, the sintering time is 1-2h, and the mixed powder is sintered into rods of φ70-80mm;

[0040] 3. The present invention adopts hot forging technology to heat the sintered blank to 650-700°C for rotary forging, and forges its outer diameter from φ80mm to 55-75mm to eliminate the internal casting defects of the material;

[0041] 4. The present invention adopts the extrusion process, preheats the forged billet to 450-500°C, keeps the temperature for 30-60 minutes, and then puts it into the extrusion equipment to extrude the billet into a φ30-35mm rod, refines the internal grain size of the material, and makes the average grain size inside the rod reach 0.02-0.03mm;

[0042] 5. The present invention adopts a surface treatment process to roll straight and peel the extruded rods for 3 to 6 times, with a peeling thickness of 0.5 to 1 mm, to fully remove defects such as cracking and oxidation on the surface of the material;

[0043] 6. The present invention adopts the rolling + drawing process, first rolling the blank into a rod of φ20-30mm, and then drawing 3-6 times to obtain the finished ceramic reinforced contact wire. The product strength is 550-594MPa, and the resistivity at 20℃ is 0.02190-0.02299Ω·mm 2 / m, Brinell hardness is 81~86HB, and the wear is only 0.001mm 2 / 10,000 bows per trip, far lower than the 0.006mm of the contact wire product 2 / Ten thousand bow sorties.

[0044] Example 1

[0045] A method for preparing a ceramic reinforced contact wire comprises the following steps:

[0046] 1. Powder making: Cu powder with a purity of more than 99.98% and a particle size of 500 mesh and Ag powder with a purity of more than 99.99% and a particle size of 500 mesh are mixed in a ratio of 999:1 to prepare copper-silver alloy powder; Al2O3 powder with a particle size of 1000 mesh and Mg2O powder are mixed in a ratio of 4:3, and then mixed into the prepared copper-silver alloy powder, and sintered after the mixture is evenly mixed;

[0047] 2. Sintering: The mixed powder is subjected to isostatic pressing sintering at a sintering temperature of 1000°C, a pressure of 5MPa, and a sintering time of 1h, and the mixed powder is sintered into a rod of φ80mm;

[0048] 3. Forging: Heat the sintered blank to 700℃ for rotary forging, and forge its outer diameter from φ80mm to 70mm to eliminate the internal casting defects of the material;

[0049] 4. Extrusion: Preheat the forged billet to 500°C and keep it warm for 30 minutes. Then put it into the extrusion equipment and extrude it into a φ30mm rod. Refine the internal grain size of the material so that the average grain size inside the rod reaches 0.03mm.

[0050] 5. Surface treatment: Roll the extruded rods straight and peel them 4 times with a peeling thickness of 1mm to fully remove surface defects such as cracking and oxidation.

[0051] 6. Rolling: Roll the peeled billet into φ20mm bars, and improve the material strength through cold rolling;

[0052] 7. Drawing: The rolled billet is drawn with 4 drawing passes to finally obtain the CTAH150 contact wire product.

[0053] Example 2

[0054] A method for preparing a ceramic reinforced contact wire comprises the following steps:

[0055] 1. Powder preparation: 99.9%wt of Cu powder and 0.1%wt of Ag powder are fully mixed to obtain copper-silver alloy powder, and then 0.4%wt of Al2O3 powder, 0.3%wt of Mg2O powder and 99.3% of the copper-silver alloy powder are mixed to obtain synthetic powder;

[0056] 2. Sintering: The synthesized powder is then subjected to isostatic pressing sintering at a sintering temperature of 1000°C, a pressure of 5 MPa, and a sintering time of 1 h to form a rod with an outer diameter of 80 mm, obtaining a ceramic phase uniformly distributed in the alloy blank;

[0057] 3. Forging: The sintered blank is hot forged. The hot forging conditions include: heating to 700℃ for rotary forging to eliminate defects such as shrinkage cavities and coarse grains on the inner wall of the material, and forging the outer diameter of the material to φ70mm;

[0058] 4. Extrusion: The forged billet is extruded. The extrusion conditions include: heating to 500°C, keeping warm for 30 minutes, and then putting it into the extrusion equipment to refine the internal grain size of the material to 0.03mm. The outer diameter of the material after extrusion is φ30mm;

[0059] 5. Surface treatment: remove oxidation, cracking and extrusion defects on the material surface by rolling and peeling;

[0060] 6. Rolling: Roll the billet to improve the strength and hardness of the material. The outer diameter of the material after rolling is φ20mm;

[0061] 7. Drawing: The finished contact wire CTAH150 is obtained through 4 drawing processes, with a strength of up to 580MPa and a resistivity of less than 0.02299Ω·mm at 20℃. 2 / m, Brinell hardness can reach 85HB, wear is 0.001mm 2 / Ten thousand bow sorties.

[0062] Example 3

[0063] A method for preparing a ceramic reinforced contact wire comprises the following steps:

[0064] 1. Powder preparation: 99.91%wt of Cu powder and 0.09%wt of Ag powder are fully mixed to obtain copper-silver alloy powder, and then 0.35%wt of Al2O3 powder, 0.35%wt of Mg2O powder and 99.3% of copper-silver alloy powder are mixed to obtain synthetic powder;

[0065] 2. Sintering: The synthesized powder is then subjected to isostatic pressing sintering at a sintering temperature of 950°C, a pressure of 4 MPa, and a sintering time of 1.5 h to form a rod with an outer diameter of 75 mm, obtaining a ceramic phase uniformly distributed in the alloy blank;

[0066] 3. Forging: The sintered blank is hot forged. The hot forging conditions include: heating to 650℃ for rotary forging to eliminate defects such as shrinkage cavities and coarse grains on the inner wall of the material, and forging the outer diameter of the material to φ65mm;

[0067] 4. Extrusion: The forged billet is extruded. The extrusion conditions include: heating to 450°C, keeping warm for 40 minutes, and then putting it into the extrusion equipment to refine the internal grain size of the material to 0.025mm. The outer diameter of the material after extrusion is φ32mm;

[0068] 5. Surface treatment: remove oxidation, cracking and extrusion defects on the material surface by rolling and peeling;

[0069] 6. Rolling: Roll the billet to improve the strength and hardness of the material. The outer diameter of the material after rolling is φ25mm;

[0070] 7. Drawing: After three drawing steps, the finished contact wire CTAH150 is obtained, with a strength of up to 560MPa and a resistivity of less than 0.02194Ω·mm at 20℃. 2 / m, hardness can reach 83HB, wear is 0.001mm 2 / Ten thousand bow sorties.

[0071] Example 4

[0072] A method for preparing a ceramic reinforced contact wire comprises the following steps:

[0073] 1. Powder preparation: 99.85%wt of Cu powder and 0.15%wt of Ag powder are fully mixed to obtain copper-silver alloy powder, and then 0.45%wt of Al2O3 powder, 0.3%wt of Mg2O powder and 99.25% of copper-silver alloy powder are mixed to obtain synthetic powder;

[0074] 2. Sintering: The synthesized powder is then subjected to isostatic pressing sintering at a sintering temperature of 900°C, a pressure of 3 MPa, and a sintering time of 2 h to form a rod with an outer diameter of 70 mm, obtaining a ceramic phase uniformly distributed in the alloy blank;

[0075] 3. Forging: The sintered blank is hot forged. The hot forging conditions include: heating to 680℃ for rotary forging to eliminate defects such as shrinkage cavities and coarse grains on the inner wall of the material, and forging the outer diameter of the material to φ55mm;

[0076] 4. Extrusion: The forged billet is extruded. The extrusion conditions include: heating to 480°C, keeping warm for 50 minutes, and then putting it into the extrusion equipment to refine the internal grain size of the material to 0.02mm. The outer diameter of the material after extrusion is φ34mm;

[0077] 5. Surface treatment: remove oxidation, cracking and extrusion defects on the material surface by rolling and peeling;

[0078] 6. Rolling: Roll the billet to improve the strength and hardness of the material. The outer diameter of the material after rolling is φ20mm;

[0079] 7. Drawing: After 5 drawing steps, the finished contact wire CTAH150 is obtained, with a strength of up to 550MPa and a resistivity of less than 0.02190Ω·mm at 20℃. 2 / m, hardness can reach 81HB, wear is 0.001mm 2 / Ten thousand bow sorties.

[0080] Example 5

[0081] A method for preparing a ceramic reinforced contact wire comprises the following steps:

[0082] 1. Powder preparation: 99.95%wt of Cu powder and 0.05%wt of Ag powder are fully mixed to obtain copper-silver alloy powder, and then 0.44%wt of Al2O3 powder, 0.25%wt of Mg2O powder and 99.31% of copper-silver alloy powder are mixed to obtain synthetic powder;

[0083] 2. Sintering: The synthesized powder is then subjected to isostatic pressing sintering at a sintering temperature of 1000°C, a pressure of 5 MPa, and a sintering time of 1.5 h to form a rod with an outer diameter of 80 mm, obtaining a ceramic phase uniformly distributed in the alloy blank;

[0084] 3. Forging: The sintered blank is hot forged. The hot forging conditions include: heating to 700℃ for rotary forging to eliminate defects such as shrinkage cavities and coarse grains on the inner wall of the material, and forging the outer diameter of the material to φ75mm;

[0085] 4. Extrusion: The forged billet is extruded. The extrusion conditions include: heating to 500°C, keeping warm for 60 minutes, and then putting it into the extrusion equipment to refine the internal grain size of the material to 0.03mm. The outer diameter of the material after extrusion is φ35mm;

[0086] 5. Surface treatment: remove oxidation, cracking and extrusion defects on the material surface by rolling and peeling;

[0087] 6. Rolling: Roll the billet to improve the strength and hardness of the material. The outer diameter of the material after rolling is φ30mm;

[0088] 7. Drawing: After 6 drawing steps, the finished contact wire CTAH150 is obtained, with a strength of up to 594MPa and a resistivity of less than 0.02231Ω·mm at 20℃. 2 / m, hardness can reach 86HB, wear is 0.001mm 2 / Ten thousand bow sorties.

[0089] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a ceramic reinforced contact wire, It is characterized in that include: The Cu powder and Ag powder are mixed to obtain copper-silver alloy powder, which is then mixed with Al 2 O 3 Powder and Mg 2 O powders are mixed to obtain synthetic powder, which is sequentially subjected to isostatic pressing, hot forging, extrusion, surface treatment, rolling and drawing to obtain a ceramic-reinforced contact wire.

2. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that In the copper-silver alloy powder, the mass percentage of Cu powder is 99.85-99.95%wt, and the mass percentage of Ag powder is 0.05-0.15%wt; in the synthetic powder, the mass percentage of Al 2 O 3 The mass percentage of the powder is 0.35-0.45%wt, Mg 2 The mass percentage of the O powder is 0.25-0.35%wt, and the mass percentage of the copper-silver alloy powder is 99.25-99.35%wt.

3. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The purity of the Cu powder is greater than 99.98%, and the particle size is greater than 400 mesh; the purity of the Ag powder is greater than 99.99%, and the particle size is greater than 400 mesh; 2 O 3 Powder size is above 1000 mesh; Mg 2 O Powder particle size is above 1000 mesh.

4. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The isostatic sintering conditions include: a sintering temperature of 900-1000° C., a pressure of 3-5 MPa, a sintering time of 1-2 hours, and sintering into a rod with an outer diameter of 70-80 mm.

5. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The hot forging conditions include: heating to 650-700° C. for rotary forging, and forging to a diameter of 55-75 mm.

6. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The extrusion conditions include: heating to 450-500° C., keeping the temperature for 30-60 minutes, and then extruding into rods with a diameter of 30-35 mm, so that the average grain size inside the rods reaches 0.02-0.03 mm.

7. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The surface treatment conditions include: rolling and peeling.

8. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The diameter of the contact line blank after rolling is 20 to 30 mm.

9. The method for preparing the ceramic reinforced contact wire according to claim 1, It is characterized in that The drawing passes are 3 to 6 passes.

10. A ceramic reinforced contact wire, It is characterized in that The ceramic reinforced contact wire is prepared by the preparation method according to any one of claims 1 to 9, wherein the strength of the ceramic reinforced contact wire is 550 to 594 MPa, and the resistivity at 20°C is 0.02190 to 0.02299 Ω·mm 2 / m, Brinell hardness is 81~86HB, wear is 0.001mm 2 / Ten thousand bow sorties.